New insights into the effects of surface nanocrystallization on the oxidation of 321 austenitic stainless steel in a humid oxygen environment at 1000 °C. (February 2019) - Pour-Ali, Sadegh; Kiani-Rashid, Ali-Reza; Babakhani, Abolfazl; Norouzi, Mohsen; Virtanen, Sannakaisa
Graphical abstract: Highlights: Effects of SNC on the oxidation behaviour of 321ASS were investigated. SNC process significantly enhanced the diffusion of Cr and Mn. Cr-vaporization remarkably affected by the SNC process. The thickness and thickness uniformity of oxide layers were affected by SNC. Schematic models were developed to describe the oxidation mechanisms. Abstract: Oxidation behaviour of surface nanocrystallized 321 austenitic stainless steel (SN–321ASS) and its conventional polycrystalline counterpart (CP–321ASS) in O2 + 10% H2 O at 1000 °C was comparatively investigated. Uniform dense distribution of high diffusivity paths on the SN-321ASS greatly enhances the Cr and Mn diffusion throughout the oxidation front. Consequently: (i) formation of a thicker Cr-rich inner oxide layer on the SN–321ASS leads to a superior oxidation resistance, (ii) formation of Mn-rich spinel oxide as a uniform intermediate layer interrupts the easy access of oxygen and/or water to the Cr-rich inner oxide layer, thereby reducing the Cr-vaporization.